Herb pair of Astragali Radix-Descurainiae Semen attenuate heart failure through the myosin VI-Tom1 complex mediated autophagy - Wang, Mengyue; Ni, Songlin; Wang, Tong; Sun, Mo; Wu, Qiaolan; Wu, Xiaolin; Lu, Guangying; Su, Peiwei; Gao, Zu; Chen, Qian (Frontiers in Cardiovascular Medicine, 2025)
Aim of the studyThis study aims to explore the therapeutic effects of Astragali Radix-Descurainiae Semen (AR-DS) on heart failure and elucidate the mechanisms behind its efficacy.Materials and methodsA rat model of heart failure was established and treated with various dosages of AR-DS decoction. Cardiac function was assessed using echocardiography, and cardiac-related mass indices were calculated. Histopathological changes were observed through HE and Masson staining. Serum levels of BNP, NT-pro BNP, and ANP were measured to evaluate AR-DS's efficacy. Electron microscopy was employed to examine the ultrastructure of cardiomyocytes, and TUNEL staining was used to assess apoptosis. Expression levels of LC3, Beclin1, p62, Myosin VI (MYO6), and Target of Myb1 (Tom1) in myocardial tissue were analyzed using qRT-PCR and Western Blot. The expression of MYO6 and Tom1 in myocardial tissue was observed through multiple immunofluorescent stainings. Protein docking was used to assess the binding energy between MYO6 and Tom1. Molecular docking to detect the binding energy and binding site of the MYO6-Tom1 complex to the major components of AR-DS.ResultsAR-DS effectively improved cardiac function and mitigated myocardial pathology in heart failure rats; it reduced serum levels of BNP, NT-pro BNP, and ANP, and suppressed cardiomyocyte apoptosis; AR-DS significantly downregulated the gene and protein expression of LC3 and Beclin1, upregulated p62, and reduced autophagy in myocardial tissue; AR-DS can effectively down-regulate the gene and protein expression of MYO6 and Tom1 in heart failure rat myocardium; protein docking results demonstrated the formation of a stable MYO6-Tom1 complex; lastly, the molecular docking results showed that the binding energies of the main components of AR-DS: Ononin, Astragaloside-IV, Rutin, Folic-acid, Daidzein, Isorhamnetin, Quercetin, Beta-Sitosterol, Kaempferol, and Formononetin can bind to the MYO6-Tom1 complex.ConclusionsAR-DS exerts a protective effect on myocardial tissue in heart failure rats by inhibiting myocardial autophagy, potentially through the modulation of the MYO6-Tom1 complex. This offers new insights into the clinical treatment of heart failure.